Potensi Bentonite Clay Dan Karbon Aktif Sebagai Aflatoksin Binders Berdasarkan Gambaran Imunologis Dan Histopatologis Pada Ayam Buras - Ramandani, Dhasia; Ummami, Risa; Hidayah, Nurulia; Dalimunthe, Naela Wanda Yusria; Indarjulianto, Soedarmanto; Yanuartono, Yanuartono; Nururrozi, Alfarisa (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
Aflatoxin is a toxic compound from the fungus A. flavus which can cause a decrease in chicken productivity. This study aims to evaluate the effect of bentonite clay and activated charcoal in chicken feed as aflatoxin binders based on histopathological and immunological features in chickens. A total of 60 chickens were randomly divided into 4 groups (G0, G1, G2, and G3) each group consisted of 15 chickens. G0 as a control without the addition of aflatoxin to the feed. Groups G1, G2, and G3’s feed were added with 106 ppb of aflatoxin. G2 was treated with 5g/kg bentonite clay, G3 was treated with 5g/kg activated charcoal. Chickens were vaccinated with Newcastle Disease (ND) on day 5. On days 14 and 28 serum was collected from the specimens for titer antibody testing. At the end of the study the chickens were dissected, the liver was taken for a histopathological test. The results of the aflatoxin level in the G0, G1, G2, and G3 groups were 10.5, 106, 19.1, and 23.95 ppb, respectively. Microscopic changes show the negative effects of aflatoxin on the liver organ. Group G0 did not show any histopathological changes, Group G2 and G3 showed several mild histopathological changes, whereas group G1 was the most severe. The antibody titers against Newcastle Disease (ND) of 4-weeks old chickens in G0, G1, G2, and G3 were 64, 4, 32, 32 HI units, respectively. The G0 treatment group has a protective titer against ND disease. Group G1 has the lowest (non-protective) ND antibody titer. Whereas the G2 and G3 groups both have protective titers against ND disease. Based on this study it was concluded that the administration of bentonite clay and activated charcoal was able to produce better immunological and histopathological features than the control group.